2019
DOI: 10.1021/acsomega.9b01576
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitosan Poly(methacrylate) Composites for Adsorption of Bromocresol Green

Abstract: In the present study, chitosan poly(methacrylate) composites were prepared and applied for adsorption of bromocresol green from aqueous solutions. The synthesized composites were characterized with scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. The bromocresol green removal by the developed adsorbent was investigated, and the effects of experimental parameters, including sample pH and adsorption time, were also examined. Furthermore, the adsorption charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…7. It is observed that 0.1 mol L −1 NaOH is the most effective regenerating solvent for the spent ChA and ChB adsorbents, 8,62 while low desorption was recorded in 0.1 mol L −1 HCl. Furthermore, 0.1 mol L −1 NaOH desorbed about 97% and 94% of the dye in the first cycle for ChA and ChB, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…7. It is observed that 0.1 mol L −1 NaOH is the most effective regenerating solvent for the spent ChA and ChB adsorbents, 8,62 while low desorption was recorded in 0.1 mol L −1 HCl. Furthermore, 0.1 mol L −1 NaOH desorbed about 97% and 94% of the dye in the first cycle for ChA and ChB, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…This variation in the removal efficiency can be explained in terms of the pK a value of BCG (p K a = 4.7). 38 In addition, the point of zero charge (PZC) of ADFS (pH = 3) was calculated experimentally by adding a constant amount of ADFS solid material to solutions of different pH values (without using a buffer solution) and measuring the final pH of the solution after a certain time of stirring. A plot of ΔpH versus the final solution pH can help in determining the PZC.…”
Section: Resultsmentioning
confidence: 99%
“…The bands observed at 2989 and bands at 1400 and 1382 cm À1 are assigned to the asymmetric vibration of -N]N-, indicating that the coupling reaction occurred and the framework of ADFS was successfully formed. 38 The absorption bands appearing at 1240 and 1058 cm À1 stand for the stretching vibrations of C-N. Moreover, the bands at 891 and 544 cm À1 correspond to -C]Cbond bending and Fe-O bond stretching, respectively.…”
Section: Characterization Of Adfsmentioning
confidence: 99%
“…Liu et al have prepared chitosan poly(methacrylate) composites, containing methacrylic acid fragments, to adsorb bromocresol green (BCG) from aqueous solutions [ 93 ]. Bromocresol is used as a pH indicator and as a tracking dye for DNA agarose gel electrophoresis.…”
Section: Polymethacrylate: Applicationsmentioning
confidence: 99%
“…The best performance was observed at pH 2; at this value a decrease of positive charge of BCG is expected, favouring electrostatic attraction and absorption of BCG onto the chitosan poly(methacrylate) surface. At pH > 2.0 a decrease of absorption efficiency was observed due to an electrostatic repulsion between BCG and anionic surface of absorbent composite [ 93 ].…”
Section: Polymethacrylate: Applicationsmentioning
confidence: 99%